Entropic bounds as uncertainty measure of unitary operators - Shamsul Shaari, Jesni; N. M. Nasir, Rinie; Mancini, Stefano (Elsevier, 2021)
We reformulate the notion of uncertainty of pairs of unitary operators within the context of guessing games and derive an entropic uncertainty relation for a pair of such operators. We show how distinguishable operators are compatible while maximal incompatibility of unitary operators can be connected to bases for some subspace of operators which are mutually unbiased.